Assessment of body frame size by elbow breadth and frame index and its relation to body composition parameters among tribal preschool children in West Bengal, India - Biswajit Mahapatra; Kaushik Bose (Wolters Kluwer Medknow Publications, 2023)
In children, body frame size estimation is used to interpret body mass and evaluate growth patterns. The present study aims to assess the body frame size by elbow breadth and frame index and its relation to body composition parameters among tribal preschool children (1-5 years of age). In the present study, 848 preschool children (430 boys and 418 girls) were included. The mean elbow breadth showed an increasing trend with increasing age, but inverse results were observed in the case of frame index. Age-wise, statistically significant sex differences were found in mean elbow breadth and frame index (except for 2 years of age). Boys show higher mean elbow breadth and frame index in all age groups, and significant sex differences were found. Elbow breadth and frame index had the strongest significant positive correlations with fat free mass (FFM) (r = 0.590, P < 0.01) and FFM index (r = 0.539, P < 0.01), respectively.